Influence of photoperiod on central appetite regulation in captive Svalbard rock ptarmigan (Lagopus muta hyperborea) - Melum, Vebjørn Jacobsen (UiT Norges arktiske universitet, 2018)
The Svalbard rock ptarmigan displays a seasonal change of body mass as a selectively beneficial adaptation for survival in the high Arctic. This physiological change is sensitive to photoperiod (daylight duration in a 24h cycle) but little is known of the mechanism through which changes in photoperiod affects body mass in this species. We exposed winer adapted Sv. rock ptarmigan to a simulated lengthening natural photoperiod (NP), constant light (LL), and constant darkness (DD). As expected, increasing photoperiod rapidly reduced body mass (BM), likely as a consequence of increased activity which occurred without compensation of increased voluntary food intake (VFI). Expression of the thyroid hormone metabolising enzyme Dio2 was quantified within the mediobasal hypothalamus (MBH), as an indicator of seasonal status. Similar to other seasonal models, Dio2 was stimulated by lengthening photoperiods and spontaneously induced by extended exposure to constant darkness. Expression of Dio2 was positively correlated with expression of NPY (a crucial appetite regulating peptide) within the Arcuate nucleus (ARC). Conversely, the expression profile of the closely associated orexigenic factor AgRP was correlated with BM, but not Dio2 levels. Expression of the satiety factor POMC was unaffected by photoperiodic changes. Collectively these data demonstrate that although photoperiod affects central gene expression in the Sv. Rock ptarmigan their expression does not directly dictate changes in VFI or BM. Instead, a more complicated pattern of appetite regulation emerges, processing photoperiodic and metabolic signals as well as seasonal behavioural changes in the Svalbard rock ptarmigan.